RAMAKRISHNA MONASTICISM AND THE CHANGING HINDU ETHOS - Swami Bhajanananda (Journal of Dharma, 1978)
The ethos of a people, a term originally used by F.H. Bradley, refers to the fundamental character or spirit of a culture. It is the underlying sentiment that informs the beliefs, customs and practices of a group or society. Every ethnos or race has its own distinctive ethos. The texture of Indian ethos consists of the warp and woof of a number of ethnic groups with caste as its dominant motif. Out of this mosaicethnos and supported by it arose the Hindu religion which is not one single religion but, like its parent base, a federation of beliefs, symbols, experiences and practices.